Efficiency of IoT technology and Associated Technologies in Research - Javad Shahrabi Farahani, Hamed Ahmadi, Alireza rivaz, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The Internet of Things' fundamental goal is to enable the automated flow of data between two systems or devices without the need for human intervention. Certain communication protocols enable this automated information sharing between two devices. The goal of this research is to determine how effective IoT technologies are in research. The descriptive-analytical research approach was used, as well as the utilization of library resources. The use of undefined networks (SDN) and increasing IoT quality indicators using SE2 and SP2 techniques, utilizing a security framework based on evolutionary algorithms to increase IoT security, and leveraging blockchain in IoT, as well as LPWAN technologies, were all investigated in this study. SP2 enhances the performance of controller plates, which can minimize service latency in spectral computing, according to the findings. By changing the number transfers in each VM independently, SE2 may give different functionality between control panels. The encryption and decryption processes employ genetic algorithm (interaction and mutation) operations, and GA (interaction and mutation) procedures are applied to each pair of blocks to aid the IoT function.